2007
DOI: 10.1016/j.dam.2006.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Computing the minimum number of hybridization events for a consistent evolutionary history

Abstract: It is now well-documented that the structure of evolutionary relationships between a set of present-day species is not necessarily tree-like. The reason for this is that reticulation events such as hybridizations mean that species are a mixture of genes from different ancestors. Since such events are relatively rare, a fundamental problem for biologists is to determine the smallest number of hybridization events required to explain a given (input) set of data in a single (hybrid) phylogeny. The main results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
132
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 21 publications
(49 reference statements)
0
132
0
Order By: Relevance
“…Wang et al (2001) considered the problem of finding a perfect phylogenetic network with recombination that has the smallest number of recombination events. They suggested that the problem is NP-hard, and a full proof was given by Bordewich and Semple (2007). Wang et al then considered a restricted problem in which all recombination events are associated with nodedisjoint recombination cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2001) considered the problem of finding a perfect phylogenetic network with recombination that has the smallest number of recombination events. They suggested that the problem is NP-hard, and a full proof was given by Bordewich and Semple (2007). Wang et al then considered a restricted problem in which all recombination events are associated with nodedisjoint recombination cycles.…”
Section: Introductionmentioning
confidence: 99%
“…That is, a forest that is maximal with respect to all agreement forests that have acyclic associated graphs has size equivalent to the hybridization number of the two trees [6]. See Figure 3.…”
Section: Subtree Prune and Regraft (Spr)mentioning
confidence: 99%
“…Hardness Results: Both of these measures, hybridization number and rSPR distance have been shown to be NP-hard and fixed parameter tractable [5,6].…”
Section: Subtree Prune and Regraft (Spr)mentioning
confidence: 99%
See 1 more Smart Citation
“…The arrival of exotic species has been well documented and geological studies give us some ability to date the fragmentation, expansion and hybridisation of our native species. New Zealand mathematicians who are developing novel methods to study hybridisation will continue to give us impact in the international scientific community (for example Huson 2005;Winkworth et al 2005;Barom et al 2006;McBreen & Lockhart 2006;Bordewich & Semple 2007;Joly et al 2007, in press a; Holland et al 2008).…”
Section: Introductionmentioning
confidence: 99%